2021
DOI: 10.3390/cancers13092031
|View full text |Cite
|
Sign up to set email alerts
|

Ductal Dilatation of ≥5 mm in Intraductal Papillary Mucinous Neoplasm Should Trigger the Consideration for Pancreatectomy: A Meta-Analysis and Systematic Review of Resected Cases

Abstract: Intraductal papillary mucinous neoplasms (IPMN) are common but difficult to manage since accurate tools for diagnosing malignancy are unavailable. This study tests the diagnostic value of the main pancreatic duct (MPD) diameter for detecting IPMN malignancy using a meta-analysis of published data of resected IPMNs. Collected from a comprehensive literature search, the articles included in this analysis must report malignancy cases (high-grade dysplasia (HGD) and invasive carcinoma (IC)) and MPD diameter so tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…In accordance with previous publications, the pancreatic main duct was considered significantly dilated if its diameter measured greater than 5 mm [ 12 , 13 ]. Normal-sized ducts were present in the majority of cases irrespective of the imaging modality employed.…”
Section: Resultsmentioning
confidence: 71%
“…In accordance with previous publications, the pancreatic main duct was considered significantly dilated if its diameter measured greater than 5 mm [ 12 , 13 ]. Normal-sized ducts were present in the majority of cases irrespective of the imaging modality employed.…”
Section: Resultsmentioning
confidence: 71%
“…In particular, an abrupt MPD change with distal pancreatic atrophy was a significant independent predictor of HG PanIN associated with IPMN (OR, 6.59, p<0.001). Many previous studies have suggested MPD dilatation to be an indicator of malignancy in IPMN [ 25 , 26 ]. Dilatated MPD may represent an indirect sign of neoplastic papillae growing into the pancreatic duct, which indicates the presence of high-grade dysplasia or invasive components [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…26 Main duct IPMNs have been reported to be a high risk factor for pancreatic cancer (odds ratio 5.66). 27 Screening and early detection Because early stage (ie, stage I, T1N0M0) disease or precancerous lesions are more likely to be curable, the goal of screening or surveillance for pancreatic cancer is to detect lesions of 2 cm or smaller, or patients with high grade dysplasia. 28 Several studies have estimated an interval of several years between a high grade dysplasia lesion (high grade PanIN and IPMN) and invasive cancer, which can give opportunities for early detection and intervention: 2.3-11 years for high grade PanIN, 29 30 and more than three years for high grade IPMN.…”
Section: Precancerous Lesionmentioning
confidence: 99%